Relationship between the Synthesis Method and the Magnetoelectric Properties of Bismuth Sodium-Potassium Titanate/Nickel Cobalt Ferrite Lead-Free Composites - Camargo, Javier Eduardo (2023)
In this work, the influence of the synthesis methods of piezoelectric and magnetostrictive phases on the final properties of the Bi0.5(Na0.8K0.2)0.5TiO3-Ni0.5Co0.5Fe2O4 composites was studied. Dif-ferent routes were used to individually synthesize each phase, and the composites were prepared using different fractions for each phase. Composites were sintered, and the structural, micro-structural, dielectric, and magnetoelectric properties were evaluated. According to the selected synthesis method employed for each phase, different particle sizes and reactivities of the indi-vidual phases were obtained. These differences determined the suitable sintering temperature for each set of composites and were responsible for the final properties. In fact, magnetoelectric properties were modulated by the combination of composition and synthesis routes.